Governance and renewable energy consumption in sub-Saharan Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2021)
The purpose of this study is to assess the nexus between governance and renewable energy consumption in sub-Saharan Africa. The focus is on 44 countries in Sub-Saharan Africa with data from 1996 to 2016. The empirical evidence is based on Tobit regressions. It is apparent from the findings that political and institutional governance are negatively related to the consumption of renewable energy in the sampled countries. The unexpected findings are clarified and policy implications are discussed in the light of sustainable development goals. This study extends the extant literature by assessing how political governance (consisting of political stability and "voice & accountability") and institutional governance (entailing the rule of law and corruption-control) affect the consumption of renewable energy in sub-Saharan Africa.
Keywords: H10; Q20; Q30; O11; O55; 330; Renewable energy; Governance; Sub-Saharan Africa; Sustainable development